Analysis Of Students' Critical Thinking Skills in Work And Energy Materials at SMA PGRI Betung - Nurazri, Mudalfy Etyanna; Marlina, Leni; Fathurohman, apit (Jurnal Pembelajaran Fisika, 2022)
Researchers conducted a study entitled analysis of students' critical thinking skills on work and energy material at SMA PGRI Betung. The type of research used is descriptive quantitative which aims to describe the critical thinking skills of high school students. The researcher chose this method because in order to get an overview of mastery students critical thinking skills. This research was conducted in the even semester of the 2021/2022 school year. The research subjects were 10th grade high school students consisting of 11 students. The results of research on critical thinking skills are produced through the provision of test instruments, namely pretests and posttests. The results obtained produced the lowest value in the aspect of critical thinking skills (KBK)the 3rd is 48.50 with a moderate presentation value. The highest value is in aspect critical thinking skills (KBK)5th at 72.73 with the high category. Critical thinking skills are also seen from the n-gain value. The result of the n-gain value is 0.44 which is in the moderate category. Therefore the category of critical thinking skills by looking at the results of the n-gain value produces an image to students that critical thinking skills must be improved. Educators must design physics learning to be even better so that it can change the skills of students. So that a change in learning design can change students and be trained in performing critical thinking skills. Increasing critical thinking skills will make students even better at learning.Keywords: Critical thinking skills, work and energy.DOI: http://dx.doi.org/10.23960/jpf.v10.n2.202203